New direction in project management success: base on smart methodology selection - Attarzadeh, I.; Ow, S.H. (2008)
Modern project management is a well-understood discipline that can produce predictable, repeatable results. The methodologies of modern project management are highly analytic, usually requiring automated tools to support them on large projects. Like most other disciplines, it is learned through both practice and study. Project management encompasses many different skills, such as understanding the interdependencies among people, technologies, budgets, and expectations; planning the project to maximize productivity; motivating others to execute the plan; analyzing the actual results; and reworking and tuning the plan to deal with the realities of what really happens as the project is executed. In order to manage a project and bring it to a successful completion, its project manager must have a complete understanding of the methodologies being used for the management of different parts of the project. Managers prefer specific project methodology, while resist and face difficulties for an opportunity to manage another project with different methodology as they don't know how much commonality exists between the preferred and the new required methodology.